Correlations among oxidative DNA damage markers, enzymatic antioxidants and HSPs in stressed rats with H2O2 at different concentrations - Younis, M. A.; Ali, S. M.; Alchalabi, A. S. (Regulatory Mechanisms in Biosystems, 2024)
Oxidative stress is a normal metabolic byproduct and when produced in abnormal amounts it leads to cellular damage indicated by oxidative DNA damage and antioxidant enzyme reduction. The present study aimed to identify the mechanism by which DNA is destroyed. Blood samples were taken from rats exposed to oral 1% and 2% hydrogen peroxide and from the control group. RNA was extracted from blood, and transcription to cDNA synthesis was done. Primers for heat shock proteins and antioxidant enzymes were designed, PCR was conducted, and serum was analysed for 8-hydroxydeoxyguanosine and tumor protein 53 by ELISA techniques. Hydrogen peroxide significantly increased the expression of 8-hydroxydeoxyguanosine and tumour protein 53. The hydrogen peroxide positively increased the expression of heat shock protein (HSP) 27 while it negatively expressed HSP90. The damage associated with DNA also impacted the gene expression of antioxidant enzymes, namely catalase, superoxide dismutase, and glutathione peroxidase. Hydrogen peroxide has induced DNA damage and could potentially regarded as a model for genetic modulation of oxidative DNA damage.